Двустворчатые моллюски надсемейства Pisidioidea (Bivalvia) крупных озер и водохранилищ Украинского Полесья - Корнюшин, А.В. (Вестник зоологии, 1993)
The data on small Pisidioidea specific composition and ecological structure in 15 lakes and Kiev water reservoir are presented. Certain problems of systemalics, occurrence and habitat distribution are discussed.